1998
DOI: 10.1046/j.1469-8137.1998.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought on non‐mycorrhizal and mycorrhizal maize: changes in the pools of non‐structural carbohydrates, in the activities of invertase and trehalase, and in the pools of amino acids and imino acids

Abstract: To study the response of non-mycorrhizal and mycorrhizal maize plants to drought, the changes in the pools of non-structural carbohydrates and amino acids were analysed in leaves and roots of two maize cvs. Plants well colonized by the arbuscular mycorrhizal fungus Glomus mosseae (Nicol. & Gerd.) (60 % of root length infected) and comparable non-mycorrhizal plants were subjected to moderate drought stress by reducing the water supply. This stress induced a conspicuous increase in the trehalose pool in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 37 publications
4
37
0
Order By: Relevance
“…In plants exposed to salinity, the total non-structural carbohydrate content in the shoots was reduced significantly compared with plants not exposed to salinity. This could indicate that salinity induces a preferential partitioning of carbohydrates to the roots, as demonstrated by Schellenbaum et al (1998). The decrease in total soluble carbohydrates due to salinity could be related also to limited carbohydrate availability, as a consequence of a decline in photosynthesis (Goicoechea et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In plants exposed to salinity, the total non-structural carbohydrate content in the shoots was reduced significantly compared with plants not exposed to salinity. This could indicate that salinity induces a preferential partitioning of carbohydrates to the roots, as demonstrated by Schellenbaum et al (1998). The decrease in total soluble carbohydrates due to salinity could be related also to limited carbohydrate availability, as a consequence of a decline in photosynthesis (Goicoechea et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Clay has capacity to retain water therefore moisture remains in the soil for more time which might affect the AMF sporulation (Dubey et al, 2008). Schellenbaum et al (1998) suggested that availability of moisture increases the growth of fungal mycelium for root colonization, leading to a decrease on AMF spore germination.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal photosynthetic conditions, most of the plant species that establish the symbiosis appear to compensate for the extra carbon demand by the root system (Harris & Paul, 1987). However, when the photosynthetic abilities of the plant are limited, the presence of the fungus in the root system might affect carbohydrate allocation as has been shown in maize in drought (Schellenbaum et al, 1998).…”
Section: mentioning
confidence: 99%